Long‐term serum bile acid concentrations in 51 dogs after complete extrahepatic congenital portosystemic shunt ligation. (29th June 2017) - Bristow, P.; Tivers, M.; Packer, R.; Brockman, D.; Ortiz, V.; Newson, K.; Lipscomb, V.
Abstract : Objectives: To report the long‐term bile acid stimulation test results for dogs that have undergone complete suture ligation of a single congenital extrahepatic portosystemic shunt. Materials and Methods: Data were collected from the hospital records of all dogs that had undergone a complete suture ligation of a single congenital extrahepatic portosystemic shunt. Owners were invited to return to the referral centre or their local veterinarian for repeat serum bile acid measurement. Dogs diagnosed with idiopathic epilepsy and undergoing bile acid stimulation tests were used as a comparison population. Results: Fifty‐one study dogs were included, with a mean follow‐up time of 62 months. 48 dogs had no evidence of multiple acquired shunts and a significant reduction in the pre‐ and post‐prandial serum bile acid concentrations at long‐term follow‐up compared with pre‐operative measurements. Pre‐ and post‐prandial serum bile acids were statistically significantly greater for dogs that had undergone a full ligation (with no evidence of multiple acquired shunts) at all time points compared to the control dogs (P<0·001 for all comparisons). Clinical Significance: The results suggest that in dogs treated with complete suture ligation mild increases in serum bile acids are not clinically relevant if there are no physical examination abnormalities, a normal body condition score and no relapse in clinical signs.